Implementasi Pengukuran Kinerja pada Pemerintah Kabupaten Lumajang dengan Menggunakan Metode Balanced Scorecard - Ningtiyas, Nurroida Bana Maulidia (Jurnal Ilmiah Mahasiswa FEB, 2016)
Balanced Scorecard was created to solve the weaknesses of performance measurement system that had been implemented before. It focuses on financial perspective only. Previously, Balanced Scorecard is only used in profit oriented organizations, but now, many public organizations also use Balanced Scorecard as one of their strategic management instruments. Local Government of Lumajang, one of the example, is a local government institution whichhas not used Balanced Scorecard for their performance measurement because itonly uses performance measurement tools which are available inthe Performance Report.This research aims to investigate the implementation and performance measurement results using the Balanced Scorecard of Local Government of Lumajang. The research usesa descriptive qualitativeresearch method by using a case study approach. The results of this study indicate the performance of the Local Government of Lumajang is categorized as fair. There three indicators used in the study which are good , fairly good or less good. Using the knowledge and capabilities, the authors sought to examine and suggest improvements in order to improve the performance measurement weaknesses of Local Government of Lumajang.Keyword : Balanced Scorecard, Local Government, Performance Measurement